Trace elements geochemistry of fractured basement aquifer in southern Malawi: A case of Blantyre rural. (July 2017) - Mapoma, Harold Wilson Tumwitike; Xie, Xianjun; Nyirenda, Mathews Tananga; Zhang, Liping; Kaonga, Chikumbusko Chiziwa; Mbewe, Rex
Abstract: In this study, twenty one (21) trace elements in the basement complex groundwater of Blantyre district, Malawi were analyzed. The majority of the analyzed trace elements in the water were within the standards set by World Health Organization (WHO) and Malawi Standards Board (MSB). But, iron (Fe) (BH16 and 21), manganese (Mn) (BH01) and selenium (Se) (BH02, 13, 18, 19 and 20) were higher than the WHO and MSB standards. Factor analysis (FA) revealed up to five significant factors which accounted for 87.4% of the variance. Factor 1, 2 and 3 suggest evaporite dissolution and silicate weathering processes while the fourth factor may explain carbonate dissolution and pH influence on trace element geochemistry of the studied groundwater samples. According to PHREEQC computed saturation indices, dissolution, precipitation and rock-water-interaction control the levels of trace elements in this aquifer. Elevated concentrations of Fe, Mn and Se in certain boreholes are due to the geology of the aquifer and probable redox status of groundwater. From PHREEQC speciation results, variations in trace element species were observed. Based on this study, boreholes need constant monitoring and assessment for human consumption to avoid health related issues. Highlights: Principal component analysis identified factors controlling trace element geochemistry. Mineral dissolution/precipitation are mechanisms controlling trace element hydrochemistry. PHREEQC geochemical modeling predicted the dominant trace element species. Elevated concentrations of Fe, Mn and Se in certain boreholes is shown.